MODIFIED RECIPROCAL TEACHING UNTUK STIMULASI KETERAMPILAN BERARGUMENTASI MAHASISWA PADA MATA KULIAH STRATEGI BELAJAR MENGAJAR BIOLOGI - Siti Murdiyah (BIOEDUKASI, 2016)
Verbal discussion and arguments required as a necessity in academic activities. Argument is an important component in critical thinking, each individual in a professional and non professional activities require arguments. Argument also has an important role in the development of science. This argumentation skills can be improved by increasing the understanding of reading as a source of learning. This study aimed to stimulate student argument skills in the subject of Teaching and Learning Strategies using learning model of reciprocal teaching. Argument skills targeted adopted Toulmin’s Model of Argument. Result showed that there were increasing quality of student’s arguments in all six parameters with parameter of data, claim and warrants showing higher enhancement relative to the other three parameters namely qualifiers, rebuttal and backup. Keywords: reciprocal teaching, keterampilan berargumentasi model Toulmin’s